Kelantan and the state economic development corporation: A study of development and the role of KSEDC in Kelantan / Nik Din Yaccob - Nik Din, Yaccob (1974)
The state of kelantan has great potential in using more natural resources, labour power, more capital or all of these in rational combination to support her 'overgroen' population on a higher level of living. Though endowed with many of these advantages she is yet unable to pull out from the stage if underdevelopment which has blanketed her for a long time. It is therefore the purpose of this study to try and look at development and its approach in kelantan and to make an evaluation in the light of socio-economic discipline. To make a thorough investigation on development as a whole in kelantan is too ambitious to say the least, in this short and concise study, especially when there are many government bodies and agencies with meriads of functions. In this situation the writer feels adequate to pick kelantan State Economic Corporation (KSEDC) as an example of an agency of development which represents social conscience. Like the corporations in other states which have been established very much earlier, KSEDC (who entered the scence in 1966) also has to face many shorcomings. It therefore contains a challenge for this corporation to undertake its duty to the population considering the present weaknesses, the competition with private enterprises, interference of political interest, the vastness of area and the ambiguity of concept in development.